Association between Myocardial Performance Index and Severity of Coronary Artery Disease Assessed with SYNTAX Score (University Heart Journal, 2018)
Background: Despite improvement in risk scoring, there are patients with stable angina identified as low risk who experience CAD events, as well as, patients deemed high risk remained free of CAD events. Invasive coronary angiogram is the gold standard method for assessment of extent and severity of CAD. However, search for additional noninvasive tool that may aid in risk discrimination is going on. Myocardial performance index (MPI) is emerging as one of them.Objective: To assess the relationship between Myocardial Performance Index and severity of coronary artery disease assessed with SYNTAX Score in chronic stable angina. Methods: This cross-sectional study was conducted in the department of Cardiology, University Cardiac Centre of BSMMU during the period of January, 2014 to December,2014 among the patients of chronic stable angina undergoing elective coronary angiogram. Total 90 patients were enrolled by random purposive sampling. All the data were recorded in structured questionnaire. Coronary angiogram with SYNTAX scoring was done during index hospital admission. Doppler study was done 1 day prior to CAG to measure MPI.Result: The mean age was found 45.5±26.1 years varied from 36 to 68 years. Male female ratio was 1.9:1. A negative significant correlation (r=-0.792; p=0.001) was found between ejection fraction (EF) and myocardial performance index (MPI). Regarding the association between risk factors with MPI status, the mean MPI was found 0.65±0.10 in diabetes mellitus and 0.57±0.10 in without diabetes mellitus. Mean MPI was significantly higher in diabetes mellitus, others risk factors are not significantly associated with MPI status. Majority (38.9%) patient’s SYNTAX score belonged to 0-22, 28(31.1%) was SYNTAX 23-32 score and 27(30.0%) was SYNTAX ≥33 score. The mean MPI was found 0.51±0.04 in low SYNTAX, 0.61±0.03 in intermediate SYNTAX and 0.74±0.07 in high SYNTAX score. The mean MPI was significantly (p22) had a 2.29 times increase (95%CI 0.16 to 33.70%) in odds of having CAD. A subject with diabetes mellitus had 1.52 times increase (95%CI 2.02 to 21.54%) in odds having CAD. Others factors are not significantly associated with CAD in Multiple regression models.Conclusion: The MPI value measured by Doppler is a cheap, radiation free, available noninvasive method and may be considered as an additional risk stratification tool beyond other investigations.University Heart Journal Vol. 13, No. 1, January 2017; 3-7